The Old Testament in the Byzantine liturgy: some remarks on the liturgical celebrations devoted to Constantinople - Casamiquela Gerhold, Victoria Errain (2016)
Some of the Byzantine liturgical celebrations devoted to the city of Constantinople were (partially) elaborated through the use of Old Testament lections. Throughout this article, we will analyze the way in which these lections were integrated into a Byzantine Christian context with the purpose of exploring some of the theological and political connotations found within the liturgical celebration of the Empire’s capital city.